Enhancing performance of Ag–ZnO–Ag UV photodetector by piezo-phototronic effect. Issue 28 (23rd April 2018) - Zhang, Xiaotong; Qiu, Yu; Yang, Dechao; Li, Bing; Zhang, Heqiu; Hu, Lizhong
Abstract : An ultraviolet photodetector based on a ZnO nanowires with metal–semiconductor–metal Schottky structure was fabricated on a flexible polyester fibre substrate. Abstract : In this work, an ultraviolet (UV) photodetector based on a ZnO nanowires (NWs) array with metal–semiconductor–metal Schottky junction structure was successfully fabricated on a flexible polyester fibre substrate by a low-temperature hydrothermal method. Subjected to a 0.2% tensile strain at −1 V, the I light and sensitivity of the as-prepared UV photodetector are lifted by 82% and 130%, respectively. Furthermore, the response speed and recovery speed are significantly raised under the same tensile strain. The working principle can be explained as that the Schottky barrier height (SBH) is effectively improved by the negative strain-induced polarization at the metal–ZnO interface which is favorable for the separation of photogenerated electron–hole pairs. This work not only provides a facile and promising means to optimize the performance of a ZnO based MSM photodetector by applying a tensile strain but also opens up the way for fabrication and integration of ZnO photodetectors on flexible polyester fiber substrates.